Disputes over Interment and Cremation: The Mediation Option - Oldfield, Yvonne (Victoria University of Wellington Law Review, 2014)
Mediation is generally perceived as comparing well to litigation in terms of cost, privacy and speed. Such practical considerations are of as much value to the parties to burial and cremation disputes as they are to the parties in many different types of dispute. Burial and cremation disputes are however particularly difficult and sensitive in nature, often involving complex cultural issues and family conflicts. These characteristic features pose challenges in the mediation context just as they do in litigation. It is argued here that mediation is well suited to addressing these challenges provided mediation style, process and delivery mechanisms are tailored appropriately. The predominant problem-solving model has limitations in meeting cultural and emotional needs, making it essential that a transformative approach informs mediation practice and procedure in relation to burial and cremation disputes. It is also argued that without their agreement to all aspects of the process, mediation of such disputes may be unsafe for the parties. In addition, where cultural differences or questions of tikanga are at issue, mandatory mediation is of questionable legitimacy. Mediation of burial and cremation disputes, particularly in the New Zealand context, can therefore occur only within a framework that upholds principles of self-determination at every level.